Entrepreneurs continous learning: assessing the preferred learning styles of SME rural entrepreneurs in Malaysia / Rafidah Abdul Rahman, Dr Zarina Salleh and Mohammmed Hardy Loh Rahim - Abdul Rahman, Rafidah; Salleh, Zarina; Rahim, Mohammmed Hardy Loh (Research Management Institute (RMI), 2012)
The purpose of this paper is to present the preferred learning styles of Small Medium Enterprise (SME) rural entrepreneurs in Malaysia. The study is conducted throughout Malaysia during Entrepreneurship Training Programs organized by Malaysian Academy of SME and Entrepreneurship Development (MASMED) in collaboration with Ministry of Rural and Regional Development Malaysia (KKLW). A self-administered survey using structured Fleming's VARK Bahasa Melayu (Malay Language) questionnaire was adopted in the study and 288 rural entrepreneurs in the training programs throughout Malaysia participated in the study. The study examines a few attributes to preferred learning styles among rural entrepreneurs in Malaysia. The findings from the attributes discovered no dominant preferred learning styles among them as the results varied among the attributes to the study. The study outcome will be used to develop a better training approach delivery in the training programs for rural entrepreneurs. In addition, it will also help both the trainers and trainees in understanding each other. Hence, the trainee will be able to learn more effectively after the precise delivery is implemented. The results is hoped to encourage trainers to be sensitive to the diversity of teaching strategies that are necessary to reach rural entrepreneurs trainees effectively.